The Dynamics of Philippines-Japan Economic Cooperation: The Case of Japan's Official Development Assistance in the Philippines - Jose V. Camacho; Agham C. Cuevas (Philippine Institute for Development Studies (PIDS), 2004)
The Japan-Philippines Economic Partnership Agreement is envisioned to further boost Japan's ODA to the Philippines, particularly for capital formation in the infrastructure sector. It will stimulate an increase in investment and capital accumulation causing more employment opportunities to be created. Output capacity will expand and so with cost of production. Moreover, export volume will increase at lower prices, thus enhancing competitiveness in the world market. Trade and business facilitation particularly among Japanese firms in the Philippines will be further enhanced due to an improvement in infrastructure and other support services, for instance, farm-to-market roads, energy, power and telecommunication, irrigation and information technology. Potential economic gains on technical assistance and development cooperation for capacity-building in the fields of information and communication technology, science and technology, intellectual property, human resource development and the enhancement of the countrys capacity to design an appropriate competition policy are evident from the Agreement. Furthermore, the proposed pact for economic partnership will be more beneficial to the Philippine economy as its institutions and their capabilities are upgraded particularly through technical cooperation in the areas of trade and investment activities, energy infrastructure development, government procurement, ecommerce and paperless trading. Philippine small-medium enterprises (SMEs) will capture immense economic benefits since the proposed economic cooperation will enhance greater trade and business facilitation. An increase in Japanese ODA channeled to the social sector will significantly improve poverty alleviation and human development. It will translate to an enhancement of skills and IT literacy that will ultimately improve the quality of labor force needed by the various sectors, particularly the industry and services. These skilled and IT-literate labor force can fill up the demand for well-trained technical professionals in Japanese economy. This will be further explored if mutual recognition of performance standards and assessment procedures of technical professionals will be agreed upon under JPEPA.
Keywords: 330; Japan-Philippines economic partnership; official development assistance (ODA); Wirtschaftsintegration; Internationale Wirtschaftsbeziehungen; Entwicklungshilfe; Japan; Philippinen